COGNITIVE CONSEQUENCES OF TRANSLATIONS FOR RENDERING THE MODALITY OF LEGAL DOCUMENTS (A SEMANTIC STUDY BASED ON THE AMSTERDAM TREATY AS AN EXAMPLE) - WAKUŁA-KUNZ, Wanda (Comparative Legilinguistics, 2009)
This study aims at examining how the manifestation forms of linguistic modality, which plays a rule-constitutive role in the content of legal documents, may be changed in the process of translation. Basing on the achievements of cognitive linguistics the author tries to find a solution for a proper translation of root and epistemic modals that would serve the same communicative function. In concluding remarks she notices that the role of linguists in solving the problems of the legal world is essential for checking the occurrence of ambiguity in the interpretation of translated texts.